Mechanical Characterization of Adobe Constructions Using Flat Jack Tests: Case Study of the Virgen de la Asunción de Sacsamarca Church - Tacas K. (2019)
This article presents the results of an experimental campaign using the flat jack technique in an adobe church called “Virgen de la Asuncion” located in Sacsamarca, Peru. The main mechanical properties of this construction were determined using the single and the double flat jack tests. The flat jack test is considered as minor destructive test (MDT), which is appropriate for historical buildings due to the temporary and easily repairable damage generated. Single and double flat jack tests were carried out on the north and east facades of the church. The single flat jack test allowed the estimation of the local compressive stress levels through the continuous monitoring of the state of strain. The double flat jack test allowed determining the local stress-strain behavior in each facade of the church. The mechanical properties obtained in this research are similar to values obtained by other authors for historical adobe buildings using different methods.